The effectiveness of private benefits in fundraising of local charities* - Sieg, Holger (2013)
This article provides an empirical analysis of the role that private benefits play in explaining charitable donations to large cultural and environmental organizations. We develop a multiple discrete choice model with differentiated products. We estimate the model using a unique data set of donor lists for the 10 largest cultural and environmental charitable organizations in the Pittsburgh metropolitan area. We find that some private benefits such as invitations to private dinner parties and special events are effective tools for fundraising. Our policy simulations suggests that the composition of private benefits has a potentially large impact on donor behavior.